Competition in California's Medi-Cal Managed Care Market Assessed by Herfindahl-Hirschman Index - Michael Tawil BS; Anthony M. DiGiorgio DO, MHA (SAGE Publishing, 2022)
Evaluating market competition is an important practice to assess how the forces and components at play in a select market interact. Healthcare markets are similar to any other market present in the world, where competition can be present or absent in the exchange of goods and services. Applying a standard measure of assessing market competition, the Herfindahl-Hirschman Index, to California's Medi-Cal managed care marketplace, it is found that there is no competition present in all of California's counties as defined by the common interpretation of the Herfindahl-Hirschman Index. A distinctive trend in markets is that when less competition is present, the cost of goods and services increases to reflect the principles of supply and demand. California Medi-Cal markets follow this trend of less competitive markets being associated with increased adult midpoint costs. These findings help further to elucidate California's Medi-Cal marketplace on a county-by county level.